INTELIJENSI PEMASARAN DALAM UPAYA MEMPERTAHANKAN KEUNGGULAN KOMPETITIF - Syukron, Miftahus; Slamet, Slamet (IQTISHODUNA, 2013)
ne" Marketing intelligence is very important for a company to maintain its competitive advantage inorder to face industrial competition. So, if it is done optimally, the information about competitors data can thenbe achieved and the company can make a decision related to the information. In reality great scale company,which is the object of the research, implement marketing inteligence based on intelligence activities, sources,and factors. Therefore, the company has to adopt the marketing intelligence system to face existing industrialcompetition and be able to apply it as the procedure. The result shows that: 1) The marketing intelligenceemployed by great scale companies uses competitive advantage planning and customer value analysis inobserving its competitor. 2) The marketing intelligence source employed by great scale companies uses twosources, company environment (internal) and outside environment of the company (external). 3) Marketingintelligence factor employed by great scale companies uses 3 factors. First, the observation of 6 main competitordata including competitor’s products, price, promotion, strategy, sale, and other data.Second, competitiveadvantage factor emphasizing on information processing related to competitor’s innovation such as productquality. Third, the salesman factor who employs person in the company to do marketing intelligence in whichthe company ability is very important in these factors application.